A construction and comprehensive analysis of the immune-related core ceRNA network and infiltrating immune cells in peripheral arterial occlusive disease - Chen, Zhiyong; Xu, Jiahui; Zha, Binshan; Li, Jun; Li, Yongxiang; Ouyang, Huan (Frontiers in Genetics, 2022)
Background: Peripheral arterial occlusive disease (PAOD) is a peripheral artery disorder that increases with age and often leads to an elevated risk of cardiovascular events. The purposes of this study were to explore the underlying competing endogenous RNA (ceRNA)-related mechanism of PAOD and identify the corresponding immune cell infiltration patterns. Methods: An available gene expression profile (GSE57691 datasets) was downloaded from the GEO database. Differentially expressed (DE) mRNAs and lncRNAs were screened between 9 PAOD and 10 control samples. Then, the lncRNA-miRNA-mRNA ceRNA network was constructed on the basis of the interactions generated from the miRcode, TargetScan, miRDB, and miRTarBase databases. The functional enrichment and protein–protein interaction analyses of mRNAs in the ceRNA network were performed. Immune-related core mRNAs were screened out through the Venn method. The compositional patterns of the 22 types of immune cell fraction in PAOD were estimated through the CIBERSORT algorithm. The final ceRNA network and immune infiltration were validated using clinical tissue samples. Finally, the correlation between immune cells and mRNAs in the final ceRNA network was analyzed. Results: Totally, 67 DE_lncRNAs and 1197 DE_mRNAs were identified, of which 130 DE_mRNAs (91 downregulated and 39 upregulated) were lncRNA-related. The gene ontology enrichment analysis showed that those down- and upregulated genes were involved in dephosphorylation and regulation of translation, respectively. The final immune-related core ceRNA network included one lncRNA (LINC00221), two miRNAs (miR-17-5p and miR-20b-5p), and one mRNA (CREB1). Meanwhile, we found that monocytes and M1 macrophages were the main immune cell subpopulations in PAOD. After verification, these predictions were consistent with experimental results. Moreover, CREB1 was positively correlated with naive B cells (R = 0.55, p = 0.035) and monocytes (R = 0.52, p = 0.049) and negatively correlated with M1 macrophages (R = −0.72, p = 0.004), resting mast cells (R = −0.66, p = 0.009), memory B cells (R = −0.55, p = 0.035), and plasma cells (R = −0.52, p = 0.047). Conclusion: In general, we proposed that the immune-related core ceRNA network (LINC00221, miR-17-5p, miR-20b-5p, and CREB1) and infiltrating immune cells (monocytes and M1 macrophages) could help further explore the molecular mechanisms of PAOD.